Child with multiple problems: Clinical complexity and uncertainty. (7th October 2018) - McDowell, Michael
Abstract: When practising neurodevelopmental–behavioural paediatrics, responsibility rests with the individual clinician to interpret research evidence in their daily work. This is not necessarily an easy task. Children do not usually present with single, easily definable problems. Complexity and uncertainty are present from the outset due to heterogeneity inherent in the diagnoses available, patterns of comorbid problems and the unique challenges of each child's social context. This article examines the resulting clinical challenge and offers potential responses. Rather than striving to eliminate uncertainty with strategies such as extensive assessment, the goal is to work effectively and efficiently within the limits of what can be readily known. Suggested strategies address complexity by considering the components of what is going on (biological, developmental, transactional) as hypotheses shared within each child's system of care. These hypotheses can then be tested and revised systematically as further information arises along the journey of treatment and longitudinal care.